2009
DOI: 10.1038/aja.2009.37
|View full text |Cite
|
Sign up to set email alerts
|

Supernumerary marker chromosome 15 in a male with azoospermia and open bite deformity

Abstract: Supernumerary marker chromosome 15 (sSMC[15]) is the most frequent marker chromosome, and it is generally regarded as unimportant if it does not contain the Prader-Willi/Angelman syndrome critical region (PWACR). The clinical importance of the larger markers in association with the critical region is mentioned in almost all reports related to marker chromosome 15, and smaller markers are solely associated with minor dysmorphic features, azoospermia and recurrent miscarriages. However, these small sSMC(15)s wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 20 publications
1
16
1
Order By: Relevance
“…The molecular analysis performed on the sSMC showed an euchromatic region (~2323 kb in size) with polymorphic genomic variants of 15 genes that were not considered to be pathogenic in the case of the patient, who was phenotypically normal. This finding seems to confirm previous data from the literature indicating a non-dose-sensitive region of chromosome 15 as containing an entire short arm, followed by a lack of euchromatin or only its small proximal part 31 32 .…”
Section: Discussionsupporting
confidence: 92%
“…The molecular analysis performed on the sSMC showed an euchromatic region (~2323 kb in size) with polymorphic genomic variants of 15 genes that were not considered to be pathogenic in the case of the patient, who was phenotypically normal. This finding seems to confirm previous data from the literature indicating a non-dose-sensitive region of chromosome 15 as containing an entire short arm, followed by a lack of euchromatin or only its small proximal part 31 32 .…”
Section: Discussionsupporting
confidence: 92%
“…Although FISH analysis suggested that the breakpoint of inv dup(15) was located between 15p11.2 and 15q11-13, the exact breakpoint and the amount of extra euchromatin or heterochromatin was not identified using the SNRPN probe in the present case. Previous studies have indicated that males with maternal-inherited sSMCs and females with paternal-inherited sSMCs were inclined to be infertile (1,3,25). However, the present study did not determine whether the presence of sSMC (15) in the proband was parentally inherited or de novo.…”
Section: Discussioncontrasting
confidence: 71%
“…Liehr and Hamid Al-Rikabi (4) pointed out that most sSMCs in infertile males were derived from acrocentric chromosomes, particularly sSMC (15), which accounted for up to 40% of all sSMCs. Patients with sSMC (15) are generally clinically normal, while the risk of oligo-or azoospermia is increased in infertile males, which may affect spermatogenesis (24,25). Further research is required on sSMC(15) due to the complex effect of the origin, size and mosaicism of this sSMC on clinical phenotypes (25,26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that sSMC may lead to reduced fertility in males without additional clinical sSMC-related symptoms [Chandley et al, 1975;Manvelyan et al, 2008a]. It is also currently thought that spermatogenesis impairment due to the presence of chromosomal abnormalities including sSMC is the main cause of oligoasthenozoospermia (OAT) [Mau et al, 1997;Koç et al, 2009]. However, little is really known about the mechanism causing this kind of infertility.…”
mentioning
confidence: 99%